PELATIHAN DIGITAL MARKETING UNTUK PENINGKATAN PENDAPATAN PETANI DI DESA BARABALI, KEC. BATUKLIANG, KAB. LOMBOK TENGAH - Sultona Osi, Zaena; Laila Zuhro, Vivin; Heriyawan; Herawaty Puna, Salvina; Putri Prastika, Silvya; Yusril Mazlan, Lalu; Walid Syuhud, Muhammad; Nesya Putri Muliadi, Fadila; Bintang, Ilham; Nurwulan Kumala, Siti; Agung Alit Triadi, Anak (Jurnal Wicara, 2025)
The digital marketing training and mentoring workshop is one of the contributions of KKN students in overcoming the problems faced by the Barabali Village community. This activity aims to provide basic understanding and practical skills in utilizing digital technology to market agricultural products of farmers in the village. The method used in this activity is observation. KKN students actively participated in the implementation of the workshop and provided guidance on digital marketing to farmers. Along with the development of technology, digital marketing is a significant opportunity for farmers to expand their market reach and increase the selling value of their products. The use of digital platforms, such as social media, has proven effective in expanding the marketing of agricultural products. Thus, digital marketing training is a relevant strategy to improve farmers' welfare in the digital era.